Impact Of Socio-Economic Factors On Postpartum Haemorrhage in Three Health Centres In Dili, Timor Leste- Cross-Sectional Study - Fernandes, Alcinda Pinto; Ariani, Novida; Wardani, Diadjeng Setya; Peguinho, Hermes; da Silva, Zelita Fernandes; da Silva, João Francisco Lela (Chakra Brahmanda Lentera Institute, 2025)
Background: Postpartum haemorrhage (PPH) is a leading cause of maternal mortality in low- and middle-income countries, including Timor-Leste. Socioeconomic factors may significantly influence the risk of PPH, yet limited local evidence is available. This study aimed to analyse the influence of education, occupation, and household income on the incidence of PPH in three Community Health Centres (CHCs) in Dili City, Timor-Leste. Methods: A cross-sectional study was conducted from January to December 2024, involving 130 postpartum mothers who delivered at CHC Comoro, CHC Becora, and CHC Vera-Cruz. Inclusion criteria were postpartum mothers aged ≥19 years, vaginal delivery at ≥37 weeks gestation, and complete medical records, including maternal and child health books or Liziu, and family socioeconomic data. Exclusion criteria included mothers with incomplete records or those who underwent medical interventions such as oxytocin induction or vacuum extraction. Data were collected retrospectively from medical records, KIA books, and antenatal care cohorts. Socioeconomic variables (education, occupation, household income) were categorised using standardised criteria. Data were analysed using chi-square tests and simple logistic regression to estimate odds ratios (OR) and 95% confidence intervals (CI). This report follows the STROBE guidelines for observational studies. Results: Most mothers (84.6%) were aged 19–34 years, and 61.5% had high-risk obstetric factors. Among respondents, 54.6% had high education, 62.3% were employed in the non-formal sector, and 64.6% had household income at or below the national minimum wage (USD 115). Only household income was significantly associated with PPH (OR = 3.309; 95% CI: 1.429–6.465; p = 0.006), indicating that mothers from low-income families had over three times higher risk of PPH. Education and occupation were not significantly associated with PPH. Conclusion: Household income is a significant socioeconomic determinant of postpartum haemorrhage in Dili, Timor-Leste. Strengthening community-based interventions targeting low-income families, including improved access to maternal health services and socioeconomic support is recommended to reduce PPH incidence